Analisis Penerapan Proyek Penguatan Profil Pelajar Pancasila SDN 1 Sumbang Kabupaten Banyumas - Aulia Nurul Isstiqomah; Yudha Febrianta (Departement of Mathematics Education, 2024)
This study aims to determine the implementation of P5 at SDN 1 Sumbang as a school that has implemented an independent curriculum in two new school years in eight classes. This school is one of the schools that adapts quickly to implement the independent curriculum in the midst of many schools that are not ready to implement the independent curriculum, especially in P5 learning. This study uses a descriptive qualitative method, with data collection techniques through interviews, observations, and document studies, as well as analysis techniques with data reduction, data presentation, and data verification. For data collection, the subjects were determined to be grade IVA teachers, principals, and students, and the object of research was P5 activities. As a result of the research, the school held a meeting to compile a team of facilitators, design and prepare P5 activities, prepare work title activities and evaluations. Teachers prepare the design of teaching modules according to their respective creativity with the theme of bineka tunggal ika, the dimension of global diversity, mutual cooperation, and creativity oriented to regional dances and replicas of traditional houses which are students' assignments with the results of their work demonstrated in the work title at the end of the semester. This research has answered how the implementation of P5 at SDN 1 Sumbang and answered efforts to improve teacher competence, performance, and creativity and improve student skills with hidden curriculum in P5 activities.